Strategi Keadilan Umar Bin Khattab dalam Pengelolaan Baitul Mal: Studi Kasus Pengelolaan Keuangan Publik di Negara-Negara Islam Kontemporer - Fahmi Nurfatwa; Dede Sansan Ramlan Sandiayana; Agung Ikram Gunawan; Lina Marlina (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Caliph Umar bin Khattab was one of the greatest leaders in Islamic history who succeeded in building a fair and transparent economic system through the establishment of Baitul Mal. This institution became the center of state financial management that accumulated funds from various sources such as zakat, kharaj, jizyah, and fa'i, then distributed them for the welfare of society. Umar applied the principles of justice, honesty, and prudence in managing the economy, including progressive fiscal policies such as pension systems, social security, and equitable budget allocation. This study uses a library research method to analyze Umar bin Khattab's economic policies and their relevance to public financial management in a Muslim-majority country like Indonesia. The results of the study show that Umar's economic principles, such as transparency, equity, and community empowerment, can be a solution to overcome the challenges of corruption, social inequality, and budget inefficiency in the modern era.